Ответ:
Объяснение:
B1. 36 - 12 = 24
36 * 2 = 72
36 + 14 = 50
36 : 4 = 9
B2. ![\frac{-5,8+3,7}{-0,3} = \frac{-(5,8-3,7)}{-0,3} = \frac{-2,1}{-0,3} = \frac{21}{3} = 7 \frac{-5,8+3,7}{-0,3} = \frac{-(5,8-3,7)}{-0,3} = \frac{-2,1}{-0,3} = \frac{21}{3} = 7](https://tex.z-dn.net/?f=%5Cfrac%7B-5%2C8%2B3%2C7%7D%7B-0%2C3%7D%20%3D%20%5Cfrac%7B-%285%2C8-3%2C7%29%7D%7B-0%2C3%7D%20%3D%20%5Cfrac%7B-2%2C1%7D%7B-0%2C3%7D%20%3D%20%5Cfrac%7B21%7D%7B3%7D%20%3D%207)
B3. 3√0,16 + √0,09 - 2√((-2)²) = 3 * 0,4 + 0,3 - 2√4 = 1,2 + 0,3 - 2 * 2 = 1,5 - 4 = -2,5
B4. -2x + 6x = 8 ; 4x = 8 ; x = 2
(x + 5) * 2 = (x - 2) * 3 ; 2x + 10 = 3x - 6 ; 6 + 10 = 3x - 2x ; x = 16
( 16 + 2 ) / 2 = 9